Functional dimorphism of two hAgRP promoter SNPs in linkage disequilibrium. Issue 5 (30th April 2004) - Bai, F; Rankinen, T; Charbonneau, C; Belsham, D D; Rao, D C; Bouchard, C; Argyropoulos, G
Abstract : The agouti related protein (AgRP) exerts its anabolic effects on food intake by antagonising the alpha-melanocyte stimulating hormone (α-MSH) at its receptors, melanocortin receptors 3 and 4 (MC3R and MC4R). A single nucleotide polymorphism (SNP) in the promoter of the human AgRP (hAgRP), −38C>T, was associated with low body fatness. The −38 T allele that was associated with low body fatness also resulted in lower promoter activity. Here we report a novel SNP, −3019G>A, again in the promoter of hAgRP, which is in complete linkage disequilibrium (LD) with the −38C>T SNP (linked alleles: −3019 A /−38 T and −3019 G /−38 C ). Functional analyses in a human adrenal and two mouse hypothalamus cell lines showed that the −3019 A allele had significantly higher promoter activity. Hence, the two linked alleles (−3019 A and −38 T ) had opposite effects on promoter function and yet they were both associated with low body fatness. The region encompassing the −38C>T SNP had approximately 1000-fold higher activity than the region encompassing the −3019G>A SNP, potentially determining the net functional effect between these two SNPs.